2016
DOI: 10.1186/s12870-016-0745-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis identifies gain and loss/change of function within the small multigenic insecticidal Albumin 1 family of Medicago truncatula

Abstract: BackgroundAlbumin 1b peptides (A1b) are small disulfide-knotted insecticidal peptides produced by Fabaceae (also called Leguminosae). To date, their diversity among this plant family has been essentially investigated through biochemical and PCR-based approaches. The availability of high-quality genomic resources for several fabaceae species, among which the model species Medicago truncatula (Mtr), allowed for a genomic analysis of this protein family aimed at i) deciphering the evolutionary history of A1b prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 70 publications
2
21
0
Order By: Relevance
“…As mentioned previously, plants also contain albumins; however, those are not phylogenetically related to the animal albumins. 39 This fact is consistent with the concept of albumin, which are water soluble, moderately soluble in concentrated salt solutions, not evolutionarily related, and experience heat denaturation. 1 Therefore, just to avoid possible confusion, for the following sections of this article, albumins solely refer to those from animals if not otherwise specified.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As mentioned previously, plants also contain albumins; however, those are not phylogenetically related to the animal albumins. 39 This fact is consistent with the concept of albumin, which are water soluble, moderately soluble in concentrated salt solutions, not evolutionarily related, and experience heat denaturation. 1 Therefore, just to avoid possible confusion, for the following sections of this article, albumins solely refer to those from animals if not otherwise specified.…”
Section: Resultssupporting
confidence: 87%
“…The detail distribution of albumins is presented in Table S1 (see supporting information). As mentioned previously, plants also contain albumins; however, those are not phylogenetically related to the animal albumins 39. This fact is consistent with the concept of albumin, which are water soluble, moderately soluble in concentrated salt solutions, not evolutionarily related, and experience heat denaturation 1.…”
Section: Resultssupporting
confidence: 82%
“…Overall, these studies suggest that both the PA1b peptides and cyclotides have evolved for plant defence. A phylogenetic analysis of the albumin-1 genes showed that the ancestral bchain gene encoded for a seed-protecting toxin [59]. The study also showed that the plant tribe Sophorae under the Fabaceae plant family contains the oldest A1b toxin to date, suggesting that the seed-protecting function of albumin-1 b-chain may have already evolved 58 million years ago [59].…”
Section: Albumin-1 Precursorsmentioning
confidence: 93%
“…Why the albumin-1 multigene family radiated extensively in C. ternatea is not known. However, the expansion of albumin-1 genes amongst Fabaceae species is not unprecedented as a study in 2016 showed that, like C. ternatea, the albumin-1 genes in Medicago truncatula also extensively diversified with 52 predicted albumin-1b peptides encoded in its genome [59]. That study showed that, in addition to having a wide tissue distribution of the A1 transcript/peptide, some of its A1b genes did not exhibit insecticidal activity, suggesting functional diversification [59].…”
Section: Albumin-1 Precursorsmentioning
confidence: 99%
See 1 more Smart Citation